Fuzzy and possibilistic co-clustering techniques for high-dimensional data analysis - Tjhi William Chandra (2008)
A study and development of a new data clustering framework called Fuzzy-possibilistic Co-clustering, which is formulated based on the hybrid of fuzzy clustering, possibilistic clustering, and co-clustering; with the objective of achieving simultaneously several goals of data analysis, namely: effective clustering of high-dimensional data, rich and natural representations of clusters, robustness to outliers, and highly-interpretable clusters